Imputed genomes of historical horses provide insights into modern breeding - Evelyn T. Todd; Aurore Fromentier; Richard Sutcliffe; Yvette Running Horse Collin; Aude Perdereau; Jean-Marc Aury; Camille Èche; Olivier Bouchez; Cécile Donnadieu; Patrick Wincker; Ted Kalbfleisch; Jessica L. Petersen; et al. (iScience, 2023)
Summary: Historical genomes can provide important insights into recent genomic changes in horses, especially the development of modern breeds. In this study, we characterized 8.7 million genomic variants from a panel of 430 horses from 73 breeds, including newly sequenced genomes from 20 Clydesdales and 10 Shire horses. We used this modern genomic variation to impute the genomes of four historically important horses, consisting of publicly available genomes from 2 Przewalski’s horses, 1 Thoroughbred, and a newly sequenced Clydesdale. Using these historical genomes, we identified modern horses with higher genetic similarity to those in the past and unveiled increased inbreeding in recent times. We genotyped variants associated with appearance and behavior to uncover previously unknown characteristics of these important historical horses. Overall, we provide insights into the history of Thoroughbred and Clydesdale breeds and highlight genomic changes in the endangered Przewalski’s horse following a century of captive breeding.